2022
DOI: 10.3390/healthcare10122511
|View full text |Cite
|
Sign up to set email alerts
|

Narratives about Negative Healthcare Service Experiences: Reported Events, Positioning, and Normative Discourse of an Active Client

Abstract: Narratives about clients’ service experiences in healthcare organizations constitute a crucial way for clients to make sense of their illness, its treatment, and their role in the service process. This is important because the client’s role has recently changed from that of a passive object of care into an active responsible agent. Utilizing Bamberg’s narrative positioning analysis as a method, and 14 thematic interviews of healthcare clients with multiple health-related problems as data, we investigated the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Patients themselves may have very different perceptions of their position on this continuum, and this warrants further investigation. Weiste and colleagues ( 2022 ), for example, found that healthcare patients with chronic conditions orient towards cultural expectations of patient activeness. In this study, when healthcare providers complained about passive patients, patient passiveness as being understandable; instead, patient activeness was seen as an expectation that everyone should adhere to.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Patients themselves may have very different perceptions of their position on this continuum, and this warrants further investigation. Weiste and colleagues ( 2022 ), for example, found that healthcare patients with chronic conditions orient towards cultural expectations of patient activeness. In this study, when healthcare providers complained about passive patients, patient passiveness as being understandable; instead, patient activeness was seen as an expectation that everyone should adhere to.…”
Section: Discussionmentioning
confidence: 99%
“…However, while complaints about patient passiveness are unproblematic from the perspective of these ideals, complaints about patient over-activeness are much more difficult to account for, due to their inherent connotations with paternalism. There is thus a need to address the discrepancy between the ways in which participants perceive and interpret trouble at work on an experiential level and the ways in which they can account for these experiences in interaction—a topic that has lately been generally addressed in various contexts and with various participants (see, e.g., Olakivi et al, 2024 ; Stevanovic et al, 2024 ; Weiste et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations